Precipitation and predation risk alter the diversity and behavior of pollinators and reduce plant fitness - Antiqueira, Pablo A. P.; Omena, Paula M. de; Goncalves-Souza, Thiago; Vieira, Camila; Migliorini, Gustavo H. [UNESP]; Kersch-Becker, Monica F.; Bernabe, Tiago N. [UNESP]; Recalde, Fatima C.; Benavides-Gordillo, Sandra; Romero, Gustavo Q. (Springer, 2020)
Biotic and abiotic factors may individually or interactively disrupt plant-pollinator interactions, influencing plant fitness. Although variations in temperature and precipitation are expected to modify the overall impact of predators on plant-pollinator interactions, few empirical studies have assessed if these weather conditions influence anti-predator behaviors and how this context-dependent response may cascade down to plant fitness. To answer this question, we manipulated predation risk (using artificial spiders) in different years to investigate how natural variation in temperature and precipitation may affect diversity (richness and composition) and behavioral (visitation) responses of flower-visiting insects to predation risk, and how these effects influence plant fitness. Our findings indicate that predation risk and an increase in precipitation independently reduced plant fitness (i.e., seed set) by decreasing flower visitation. Predation risk reduced pollinator visitation and richness, and altered species composition of pollinators. Additionally, an increase in precipitation was associated with lower flower visitation and pollinator richness but did not alter pollinator species composition. However, maximum daily temperature did not affect any component of the pollinator assemblage or plant fitness. Our results indicate that biotic and abiotic drivers have different impacts on pollinator behavior and diversity with consequences for plant fitness components. Even small variation in precipitation conditions promotes complex and substantial cascading effects on plants by affecting both pollinator communities and the outcome of plant-pollinator interactions. Tropical communities are expected to be highly susceptible to climatic changes, and these changes may have drastic consequences for biotic interactions in the tropics.
Keywords: Plant-pollinator interactions; Predation; Visual cues; Climatic conditions; Cascading effect